Analisis Tingkat Pendapatan Dan Pengetahuan Zakat Terhadap Ketaatan Membayar Zakat Baznas Kota Tasikmalaya - Gista Rismayani; Suhendri; Yeni Fitriani Somantri (Jurnal Akuntansi dan Audit Syariah)
Based on a survey of researchers to the National Amil Zakat Agency (BAZNAS) Tasikmalaya City. That the ability to report zakat in Tasikmalaya City is very large annually but in reality the total zakat that BAZNAS is able to collect is less than 50%. The data shows that the amount of zakat fund collection has not reached what is expected from this potential. This study aims to determine the effect of income levels and zakat knowledge on obedience in paying zakat. This research is a field research using a quantitative approach. The type of this research is in the form of associative descriptive research. The data analysis technique in this study is multiple regression analysis. The results showed that income levels had a significant effect on citizen compliance in paying zakat at BAZNAS Tasikmalaya City and knowledge of zakat had no significant effect on citizen compliance in distributing zakat at BAZNAS Tasikmalaya City, while simultaneously the level of reporting and knowledge of zakat had a significant effect on citizen obedience in distributing zakat to BAZNAS Tasikmalaya City.